3D motion analysis of latissimus dorsi tendon transfer in patients with posterosuperior rotator cuff tears: analysis of proprioception and the ability to perform ADLS - Hetto, Pit; Erhard, Sarah; Thielen, Mirjam; Wolf, Sebastian Immanuel; Zeifang, Felix; Drongelen, Stefan van; Maier, Michael Wolfgang (Orthopaedics & traumatology, 2020)
Background - Massive irreparable posterosuperior rotator cuff tears may result in a loss of external rotation. Most of these patients lose their ability to perform activities of daily living (ADLs), especially where external rotation and abduction are needed. Latissimus dorsi tendon transfer (LDTT) is a method to restore abduction and external rotation in patients with posterosuperior rotator cuff tears. There are no objective data concerning whether LDTT can restore range of motion (ROM), especially in performing ADLs and if proprioception changes after LDTT. - Methods - We examined 12 patients 4.2 years (1-9 years) after LDTT with simultaneous 3D motion analysis; the opposite, nonaffected side was assessed as control. The measurement protocol included maximum values in flexion/extension, abduction/adduction, internal/external rotation in 0° and in 90° flexion and in 90° abduction. To evaluate competences, we measured seven activities of daily life and examined the proprioceptive ability using an active angle reproduction test. - Results - In total, 4.2 years (1-9 years) after LDTT there was no significant difference in flexion/extension and abduction/adduction compared to the healthy side. Maximum external rotation was significantly reduced compared to the opposite side. Eleven patients (85%) were able to perform all ADL. Proprioceptive ability did not differ from the healthy side. - Conclusion - LDTT cannot fully restore a patient's ability for external rotation after a posterosuperior rotator cuff tear. However, 4.2 years after surgery, 85% of the patients are able to perform all ADLs. Proprioceptive ability is not affected by the transfer.
Online 11 December 2019
Gesehen am 21.04.2020